Hening, 1 Statutes at Large Act 10 at 226 (1823) - (:unkn) unknown (My University, 1680)
"ALL persons except negroes to be provided with arms and amunition or be fined at pleasure of the Governor and Council."
Keywords: REQUIRED POSSESSION